Review of the Political Direction of National Legal Development Law - Hamzani, Achmad Irwan; Rahayu, Kanti; Haryadi, Tani; Khasanah, Nur; Aravik, Havis (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2021)
The political direction of the law in Indonesia in the development of national law simplifies legislation. The scope of national legal development is not only through legislation. There is the functionalization of the law that lives in society. The purpose of the research describes the political urgency of law in the development of national law and reviews the political direction of national law development law. This research uses a philosophical approach, namely to examine the law from the ideal side in the form of an idea of the direction of national law politics in the future. The results of this study show that the politics of law is necessary to provide direction in the development of national law. Each country has a legal political direction whose role as the basic policy of state organizers to determine the direction, shape, and content of the law to be established. Legal politics as a strategy of the formation process, as well as the implementation of laws based on the national legal system to achieve the goals and ideals of the state. The political direction of the law in Indonesia in the development of national law simplifies legislation.Keywords: The Political Direction of Law; The Development of National Law; The Living Law Tinjauan Arah Politik Undang-Undang Pembangunan Hukum Nasional AbstrakArah politik hukum di Indonesia dalam pembangunan hukum nasional menyederhanakan pada legislasi. Cakupan pembangunan hukum nasional sebenarnya tidak hanya melalui legislasi. Ada fungsionalisasi hukum yang hidup di masyarakat. Tujuan penelitian mendeskripsikan urgensi politik hukum dalam pembangunan hukum nasional, dan mereview arah politik hukum hukum pembangunan hukum nasional. Penelitian ini menggunakan pendekatan filosofis, yaitu mengkaji hukum dari sisi ideal berupa gagasan arah politk hukum nasional ke depan. Hasil penelitian ini menunjukan bahwa politik hukum sangat diperlukan guna memberikan arah dalam pembangunan hukum nasional. Setiap negara memiliki arah politik hukum yang perannya sebagai kebijakan dasar penyelenggara negara untuk menentukan arah, bentuk maupun isi hukum yang akan dibentuk. Politik hukum sebagai strategi proses pembentukan, serta pelaksanaan hukum yang berpijak pada sistem hukum nasional untuk mencapai tujuan dan cita-cita negara. Arah politik hukum di Indonesia dalam pembangunan hukum nasional menyederhanakan pada legislasi.Kata Kunci: Arah Politik Hukum; Pembangunan Hukum Nasional; The Living Law Обзор политической направленности национального закона о правовом развитии Аннотация:Направление правовой политики Индонезии в развитии национального права упрощено до законодательного. На самом деле, развитие национального права осуществляется не только через законодательство. Существует действующий закон, который живет в обществе. Цель исследования - описать актуальность правовой политики в развитии национального права и рассмотреть направление правовой политики в развитии национального права. В данном исследовании используется философский подход, который рассматривает право с идеальной стороны в виде идей политического направления национального права в будущем. Результаты этого исследования показывают, что правовая политика необходима для определения направления развития национального права. В каждой стране существует правовое политическое направление, роль которого заключается в том, чтобы руководствоваться государственной администрацией в качестве основной политики по определению направления, формы и содержания закона, который должен быть сформирован. Правовая политика как стратегия процесса формирования и реализации закона основана на национальной правовой системе для достижения целей и идеалов государства. Направление правовой политики Индонезии в развитии национального права упрощено до законодательного.Ключевые Слова: Направление Правовой Политики; Развитие Национального Права; Живое Право